Islamic economics and finance an epistemological inquiry - Baltagi, Badi H.; Sadka, Efraim; Choudhury, Masudul Alam, 1948- (Contributions to economic analysis ;, 2011)
Islamic Economics and Finance: An Epistemological Inquiry is a scholarly work on the foundations of the role that the moral and ethical law plays on human enterprise comprising economics, finance, society and science. Divided into three parts, theoretical, empirical and application, the study covers a vast area of socio-scientific investigation and is extensively comparative in perspective. Its methodology is a mix of a textual, analytical, diagrammatic, mathematical and applied nature spanning various problems of Islamic economics, finance, society and science within a general-system worldview of unity of knowledge. This book presents multidimensional general-system conception, construction, formalism, application and inference as empirically viable and explainable and uses the language of philosophy of science and applied mathematical models alongside policy analysis. At a time when an epistemological study of the foundations of Islamic economics, finance, society and science is receiving crucial attention worldwide this text is equally accessible to the informed reader and the specialized one.